The impact of environmental and silvicultural factors on facilitation and competition processes in pure and mixed plantations of Eucalyptus e Acacia mangium - Oliveira, Ivanka Rosada de (2020)
Mixed forest plantations of N2 -fixing trees (NFT) and non- N2 -fixing trees (non-NFT) have been proposed to increase productivity and ecosystem services in regions with N- deficient soils. These intercropped systems can increase availability, use, and efficiency of natural resources (light, water, nutrients) when compared to monocultures. However, mixed- species plantations in Brazil cover a very small area in comparison to monocultures. To overcome this situation, studies must be carried out on the relationships between species, soil, and climate conditions, and management techniques by characterizing ecosystem functions and interactions to increase productivity of mixed-species plantations compared to monocultures, in an ecologically friendly and efficient way. Our study aimed to gain insights into facilitation and competition processes in pure and mixed-species plantations of Eucalyptus and Acacia mangium. The thesis is structured in three main parts where we aimed to better understand the ecological processes of pure and mixed-species plantations under contrasting silvicultural and edaphoclimatic conditions. We used 15N isotopic tracer, MAESTRA model, and inventory and biomass data to assess the effects of competition and facilitation process in pure and mixed-species plantations of Eucalyptus and Acacia mangium under contrasting nutrient supply, different planting densities, and spatial arrangements, as well as different climatic and soil conditions. In the first part, our results showed that the N released from forest floor decomposition was 31% higher in fertilized than in unfertilized plots, and that short-term belowground N transfer from Acacia to Eucalyptus was found close to harvest age and higher with lower nutrient supply. In the second part, we showed that the differences between treatments in the stem biomass growth (SBG) of Eucalyptus was mainly explained by differences in light absorption, while the differences in SBG of Acacia was explained by light absorption and light use efficiencies. The highest stand productivity was observed in 100E with 1666 trees ha-1. However, Eucalyptus in the arrangement 33A:67E with 1111 trees ha-1 had a greater SBG than in 50A:50E and a similar production than in 100E. Moreover SBG, light absorption and light use efficiency of Acacia resulted from the combined effects of stand density and presence of Eucalyptus, while for Eucalyptus these variables were strongly dependent on Eucalyptus stand with low or no impact of Acacia. In the third part, our results showed that stressful conditions, such as hotter droughts, led to higher Eucalyptus mortality in Sinop-MT and higher Acacia mortality rates in Colinas-TO. The greatest growth and highest biomass production of Eucalyptus trees was found in Itatinga-SP, while the highest tree growth and stand production for Acacia occurred in Sinop- MT. Our results provided insights into how silvicultural practices may impact the behavior of pure and mixed-species plantations of Eucalyptus and Acacia mangium and how changes in climate and soil properties may affect the survival and development of each species. In this project, we stressed the interest to associate Acacia to Eucalyptus in forest plantations to limit N eucalypt deficiencies when stands are established in low-fertility soils and/or fertilizers are not applied. We highlighted the importance to define optimal planting design and planting density to improve forest production, as well as account for climatic, and soil characteristics under stressful conditions to avoid large mortality rate and promote sustainable forest plantation management.